Osteosarcoma - Biology, Behavior and Mechanisms 2017
DOI: 10.5772/67448
|View full text |Cite
|
Sign up to set email alerts
|

Immune Environment and Osteosarcoma

Abstract: Immune niche with its huge cell diversity including more speciically tumour iniltrating lymphocytes (TILs), tumour-associated macrophages (TAMs) regulate osteosarcoma (OS) microenvironment. TAMs exert diferential activities in the tumour development according to their polarisation. Indeed, in oncology, M1-polarised macrophages are considered as anti-tumour efectors, and M2-polarised macrophages are deined as protumour modulators by increasing the neoangiogenic process. TAM density is correlated with tumour cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, activated M2-like macrophages exhibited low antitumour activity, and growth of tumour cells was only reduced when the anti-EGFR antibody cetuximab was co-administered to cancer cells in a process involving antibody-dependent cell-mediated phagocytosis [ 179 ]. The main role of liposomal mifamurtide may be inducing the expression of proinflammatory cytokines that lead to an M1 macrophage response [ 180 ].…”
Section: Nanomedicines To Modulate the Tme And Icdmentioning
confidence: 99%
“…On the other hand, activated M2-like macrophages exhibited low antitumour activity, and growth of tumour cells was only reduced when the anti-EGFR antibody cetuximab was co-administered to cancer cells in a process involving antibody-dependent cell-mediated phagocytosis [ 179 ]. The main role of liposomal mifamurtide may be inducing the expression of proinflammatory cytokines that lead to an M1 macrophage response [ 180 ].…”
Section: Nanomedicines To Modulate the Tme And Icdmentioning
confidence: 99%
“…In general, we found that high levels of CD8 T cells and M1 Macrophages are associated with good prognosis, while a high level of M0 Macrophages correlates with poor prognosis in osteosarcoma. These results make sense because CD8 T cells are known to kill cancer cells directly [ 47 , 48 ] and M1 Macrophages exhibit anti-tumor effects by producing cytokines that inhibit osteosarcoma growth [ 49 ]. These facts could also explain the observed differences between the outcomes of patients in clusters 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…TGF- and IL-10 are secreted by helper T cells, M2 macrophages, and cancer cells [ 32 , 33 , 35 , 65 , 66 , 67 ]. IL-4 and IL-13 are secreted by helper T cells and M2 macrophages [ 32 , 65 , 68 ]. Thus, we model the dynamics of as: …”
Section: Methodsmentioning
confidence: 99%
“… consists of IL-6 and IL-17, where IL-6 is produced by M1 macrophages, helper T cells, and cancer cells [ 33 , 36 , 65 , 67 , 69 ], and IL-17 is produced by helper T cells [ 32 ]. The corresponding equation for is: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation